Swedish Bible 1873 - Språkbanken Text (University of Gothenburg, 2024)
The first Swedish translation of the Bible came in 1541, by order from Gustav Vasa. After that, there would not be another full translation until 1917. But the Swedish language and orthography changed a lot during this time, and so several intermittent versions were made. Two modernised versions based on the 1541 translation had official status, 1618 and 1703.
During the 1800s, many new religious movements spread in Sweden and the world, so the need for a more modern and legible Bible grew. This version came out in 1873 (Bibelen eller Den heliga skrift) and is based on the 1703 version. It was funded by organisations in the UK.
The text can be read at bible.com, and the 170 version is available at Litteraturbanken.

Den första svenska översättningen av Bibeln kom 1541, på uppdrag av Gustav Vasa. Därefter skulle det dröja ända till 1917 innan en helt ny översättning kom ut. Men språket och skriften förändrades en hel del under tiden, och därför gjordes flera nyare versioner som bygger på Gustav Vasas bibel. Två var officiella revisioner, 1618 och 1703.
Under 1800-talet växte flera frikyrkor fram i Sverige, och man såg behov av en bibelöversättning som var lättare att läsa. Den version vi ser här gavs ut 1873 (Bibelen eller Den heliga skrift), och bygger på en ytterligare modernisering av versionen från 1703.
Denna version finns att läsa på bible.com. Versionen från 1703 finns på Litteraturbanken.
Bibeln 1873
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik